Fig. 1 in High Toxocara cati prevalence in wild, free-ranging Eurasian lynx (Lynx lynx) in Finland, 1999-2015 - Virta, Miisa; Huitu, Otso; Heikkinen, Juha; Holmala, Katja; Jokelainen, Pikka (Zenodo, 2022)
Fig. 1. The head, the cephalic alae and the body of the Toxocara cati found from female Eurasian lynx (Lynx lynx) from Finland. The measurement scale has red marks at 1 mm intervals. (For interpretation of the references to colour in this figure legend, the reader is referred to the Web version of this article.) Published as part of Virta, Miisa, Huitu, Otso, Heikkinen, Juha, Holmala, Katja & Jokelainen, Pikka, 2022, High Toxocara cati prevalence in wild, free-ranging Eurasian lynx (Lynx lynx) in Finland, 1999-2015, pp. 205-210 in International Journal for Parasitology: Parasites and Wildlife 17 on page 207, DOI:10.1016/j.ijppaw.2022.02.004, http://zenodo.org/record/13287925